Load sharing within a human thoracic vertebral body: An in vitro biomechanical study - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2007)
OBJECTIVE: The vertebral body is the major load bearing part of the vertebra and consists of a central trabecular core surrounded by a thin cortical shell. The aim of this in vitro biomechanical study is to determine the debated issue of load sharing in a vertebral body. METHODS: A series of non-destructive compressive testing on excised human thoracic vertebral bodies were performed. The testing process consisted of a stepwise removal of the vertebrae's trabecular centrum and measurement of surface strains. RESULTS: Load sharing of cortical shell of osteopenic vertebrae (48.1+/-7.6) was significantly higher than that of normal vertebrae (44.3+/-10.6). Load sharing of middle thoracic vertebrae (49.4+/-10.0) was significantly higher than that of lower thoracic vertebrae (42.4+/-8.5). According to general linear model analysis, test speed and load were not found to be effectual on load sharing with the exception that osteopenic vertebrae showed lower cortical load sharing under higher loads. CONCLUSIONS: The cortical shell takes nearly 45% of physiological loads acting upon an isolated thoracic vertebra. Load sharing between cortical shell and trabecular centrum is significantly affected by spinal level and bone mineral density. The load borne by trabecular bone increases towards the lower spinal levels, and decreases by osteoporosis.
Keywords: biomechanics; bone; osteoporosis; spine; test; thoracic vertebrae; QUANTITATIVE COMPUTED-TOMOGRAPHY; LUMBAR VERTEBRAE; TRABECULAR BONE; SURFACE STRAIN; FRACTURE RISK; COMPACT-BONE; STRENGTH; OSTEOPOROSIS; COMPRESSION; PREDICTION